Lethe's law : justice, law and ethics in reconciliation - Christodoulidis, Emilios; Veitch, Scott (Hart Pub., 2001)
This book offers a series of original essays by an international group of scholars whose work looks comparatively at laws attempts to deal with the past. Ranging from questions of criminal responsibility and amnesty to those of laws relation to time, memory, and the ethics of reconciliation, it is a sustained jurisprudential and philosophical analysis of one of the most important and pressing legal concerns of our time. Among its key concerns is that justices demand on law has changed and, in the face of a divided and violent past, law is being called on to do the kind of work it ordinarily.